Проблемні питання робочого часу науково-педагогічних працівників закладів вищої освіти зі специфічними умовами навчання - Дегтярьова, В. О.; Dehtiarova, V. O.; ORCID: https://orcid.org/0000-0002-9816-8762 (Вісник Харківського національного університету внутрішніх справ. – 2022. – № 3 (98). – С. 67-76, 2022)
Досліджено підходи вчених щодо дефініції «робочий час». Розкрито основні проблемні питання робочого часу науково-педагогічних працівників закладів вищої освіти зі специфічними умовами навчання та запропоновано пріоритетні шляхи їх вирішення.

The article is devoted to problematic issues of working hours for scientific and pedagogical workers of higher education institutions with specific conditions of training. The approaches of the scientists regarding the definition of “working hours” have been studied. A comparison of the working hours of scientific and pedagogical workers and police officers who are sent to the positions of scientific and pedagogical workers for further service has been made in accordance with the current legislation. The analysis of normative legal acts regulating the activities of scientific and pedagogical workers has been carried out. Local acts adopted by institutions of higher education within their competence and with the help of which standards of working hours for the main types ofeducational, methodical, scientific, organizational work of scientific and pedagogical workers are established have been analyzed. The recommended list of the types of educational, methodical, scientific and organizational work for scientific and pedagogical, scientific and pedagogical workers in accordance with the Order of the Ministry of Education and Science of Ukraine “On approval of the Recommended list of types of educational, methodical, scientific and organizational work for scientific and pedagogical, scientific and teaching staff” has been considered. The main problematic issues of the working hours for scientific and pedagogical workers of higher education institutions with specific training conditions have been revealed and priority ways of solving them have been proposed.

Исследованы подходы ученых относительно дефиниции «рабочее время». Раскрыты основные проблемные вопросы рабочего времени научно-педагогических работников учреждений высшего образования со специфическими условиями обучения и предложены приоритетные пути их решения.
Problematic issues of scientific and pedagogical workers’ working hours at higher education institutions with specific training conditions
Дегтярьова, В. О. Проблемні питання робочого часу науково-педагогічних працівників закладів вищої освіти зі специфічними умовами навчання / Вікторія Олександрівна Дегтярьова // Вісник Харківського національного університету внутрішніх справ. – 2022. – № 3 (98). – С. 67-76. - DOI: https://doi.org/10.32631/v.2022.3.06.
Keywords: Трудове право. Право соціального забезпечення. Labor law. Law of social guaranteeing. Трудовое право. Право социального обеспечения; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; робочий час; working hours; рабочее время; науково-педагогічні працівники; scientific and pedagogical workers; научно-педагогические работники; заклади вищої освіти зі специфічними умовами навчання; institutions of higher education with specific conditions teaching; заведения высшего образования со специфическими условиями обучения; працівники Національної поліції України; employees of the National Police of Ukraine; работники Национальной полиции Украины